2016
DOI: 10.1016/j.jash.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of adherence to healthy lifestyle behaviors among hypertensive adults in the 50 states and the District of Columbia, 2013

Abstract: Achieving and maintaining a healthy lifestyle is an important part of hypertension management. The purpose of this study was to assess US state-level prevalence of adherence to healthy lifestyle behaviors among those with self-reported hypertension. Using 2013 data from the Behavioral Risk Factor Surveillance System, a state-based telephone survey, we examined the adherence to 5 healthy lifestyle behaviors related to hypertension management: having a “normal” weight, not smoking, avoiding or limiting alcohol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
1
24
2
Order By: Relevance
“…Overall, the prevalence of healthy lifestyle behaviors varied widely among those with self-reported hypertension: 20.5% had a normal weight, 82.3% did not smoke, 94.1% reported no or limited alcohol intake, 14.1% consumed the recommended amounts of fruits or vegetables, and 46.6% engaged in the recommended amount of PA. 4 …”
Section: High Blood Pressurementioning
confidence: 99%
“…Overall, the prevalence of healthy lifestyle behaviors varied widely among those with self-reported hypertension: 20.5% had a normal weight, 82.3% did not smoke, 94.1% reported no or limited alcohol intake, 14.1% consumed the recommended amounts of fruits or vegetables, and 46.6% engaged in the recommended amount of PA. 4 …”
Section: High Blood Pressurementioning
confidence: 99%
“…Per estimates derived from the 2013 Behavior Risk Factor Surveillance Survey, the prevalence of diagnosed hypertension is 32.5% [ 16 ], with ethnic minorities disproportionately affected. The overall prevalence of diagnosed hypertension in the 2013 NHIS was 24% [ 17 ]; Asian and White adults reported lower rates of diagnosed hypertension than Blacks.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of hypertensive patients in Turkey revealed a better medication adherence behavior, such that 78% of patients were reported to adhere to the prescribed anti-hypertensive medication, while the adherence to lifestyle modifications was only 42% [16]. A secondary analysis on an American national survey reported only 1.7% of hypertensive patients followed all five components of lifestyle modifications [17]. Low adherence to lifestyle modifications was highlighted among hypertensive patients, as the use of medication alone was not enough to control BP [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%